2020
DOI: 10.1002/syst.202000052
|View full text |Cite
|
Sign up to set email alerts
|

Folding Stability and Self‐Association of a Triplet‐Repeat (CAG)20 RNA Hairpin in Cytomimetic Media

Abstract: RNA molecules with trinucleotide repeat expansions are involved in the pathology of various neurodegenerative diseases, such as Huntington's disease. A central research objective is to understand how trinucleotide repeat RNAs fold and function in disease progression. Studies that investigate the sequence structure, stability and self‐assembly of such RNAs mainly focused on in vitro methods in dilute aqueous solution. Functional studies in cells reveal further aspects of transport, protein association or assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 55 publications
(143 reference statements)
0
17
0
Order By: Relevance
“…It is well known that the structure and thus the function of RNAs such as RNA‐G4Qs are very susceptible to changes in their environment, that is, they respond sensitively to the presence of salts, osmolytes, crowding agents, and to the binding of proteins, which are also abundant in the biological cell. [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] In general, the stability of quadruplex structures is determined by H‐bonds between nucleobases, π‐stacking interactions between neighboring base pairs, counterion condensation at the phosphate backbone by cations, hydration changes, and by changes in conformational entropy. [11] Recently, it has been observed that the stability of the G4Qs depends also on the number of G‐quartets.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the structure and thus the function of RNAs such as RNA‐G4Qs are very susceptible to changes in their environment, that is, they respond sensitively to the presence of salts, osmolytes, crowding agents, and to the binding of proteins, which are also abundant in the biological cell. [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] In general, the stability of quadruplex structures is determined by H‐bonds between nucleobases, π‐stacking interactions between neighboring base pairs, counterion condensation at the phosphate backbone by cations, hydration changes, and by changes in conformational entropy. [11] Recently, it has been observed that the stability of the G4Qs depends also on the number of G‐quartets.…”
Section: Introductionmentioning
confidence: 99%
“…A recent example using HeLa cell lysate as cytomimetic media showed it promoted self-association of disease-associated RNA aggregates. [25] Although artificial crowding agents mimic the crowded cellular interior and dilute lysates mimic attractive and repulsive interactions, in-cell studies demonstrate that in-cell RNA behaviors cannot be reproduced by crowding or sticking agents alone. [20] Recently, we demonstrated that a combination of crowding and sticking agents, 150 g/L Ficoll and 60 % lysis buffer, could be used as an in vitro mimic that accounts for both steric crowding and non-steric sticking effects on cytoplasmic protein stability and kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Dilute cell lysates or lysis buffer are commonly used to replicate sticking trends observed in cells. A recent example using HeLa cell lysate as cytomimetic media showed it promoted self‐association of disease‐associated RNA aggregates [25] . Although artificial crowding agents mimic the crowded cellular interior and dilute lysates mimic attractive and repulsive interactions, in‐cell studies demonstrate that in‐cell RNA behaviors cannot be reproduced by crowding or sticking agents alone [20] …”
Section: Introductionmentioning
confidence: 99%
“…Despite the major destabilization, it is important to note that the RNA was still mostly folded under physiological conditions (Δ G u θ,37 ° C (cytosol) = 6.8 ± 2.1 kJ/mol, meaning that only 6.7% of the RNA was unfolded at 37 °C). The decrease in Δ G u θ,37 ° C was also large compared to that under any in vitro condition measured previously (e.g., Δ G u θ,37 ° C (DPBS + 300 g/L Ficoll 70) = 18.0 ± 1.0 kJ/mol; Δ G u θ,37 ° C (DPBS + 300 g/L ethylene glycol) = 12.0 ± 3.0 kJ/mol; Δ G u θ,37 ° C (HeLa cell lysate) = 13.3 ± 0.5 kJ/mol) . Thus, crowding effects such as the decrease in water activity or non-specific interactions of the RNA and cosolutes could not solely account for the observed decrease in folding stability.…”
Section: Resultsmentioning
confidence: 87%
“…In preliminary work, we prepared (CAG) 20 RNA for FReI experiments by terminal FRET labeling using Alexa Fluor 488 at the 5′-end and Alexa Fluor 594 at the 3′-end. Dyes were covalently connected to the RNA backbone via C6 linkers and by alkyne–azide click chemistry (5′-end) or amine coupling to a carbonic acid N-hydroxy succinimide ester (3′-end) (Figure A).…”
Section: Resultsmentioning
confidence: 99%